Thyroid Dysfunction following Radiotherapy and Combined Therapy in Non-Thyroid Head and Neck Cancers - Rais Ahmad Bhat; Om Prakash; Shabab Lalit Angurana (Bengal Journal of Otolaryngology and Head Neck Surgery)
INTRODUCTION: In patients with head and neck cancers thyroid gland bears the brunt in terms of either excision or irradiation resulting in loss of functionality of the gland leading to thyroid dysfunction. The purpose of this study was to evaluate thyroid function following radiotherapy and combined therapy in non-thyroid head and neck cancers.